What is the EU-UK relation all about? Tracking the path from monetary integration to "ever closeness" - Corrado Macchiarelli (London School of Economics and Political Science (LSE), European Institute, 2018)
The history of European integration has been characterized by several 'stops-and-goes' with considerable support on political grounds. In this paper, we discuss the role of European integration for the future of the EU-UK relations. Integration, consistent with the idea of 'completing' the European Monetary Union (hence, a 'Genuine Economic and Monetary Union'- GEMU), will have the obvious consequence of affecting the UK as well and the future of its negotiations with the EU. Provided that European integration worked in the past, the net benefits of staying out of the EU exante may be different from the same benefits ex-post, particularly in the likely scenario that the Union will have to 'comprehensively' move towards a GEMU to safeguard its integrity.
Keywords: 330; EMU; European integration; Brexit